The impact of interactive video-based exercise on quality of life among pregnant women in Indonesia: A pilot study - Dewi Marfuah; Tukimin bin Sansuwito; Rathimalar Ayakannu (JKP (Jurnal Keperawatan Padjajaran), 2025)
Background: Pregnant women experience lower quality of life compared to the general population and experience a decrease in their quality of life as their pregnancy progresses. Video interactive provides an interesting and interactive environment, so participants would be more likely to enjoy completing their physical activity regimen.